2020
DOI: 10.1029/2020jg005924
|View full text |Cite
|
Sign up to set email alerts
|

Soil Respiration Response to Rainfall Modulated by Plant Phenology in a Montane Meadow, East River, Colorado, USA

Abstract: Soil respiration is a primary component of the terrestrial carbon cycle. However, predicting the response of soil respiration to climate change remains a challenge due to the complex interactions between environmental drivers, especially plant phenology, temperature, and soil moisture. In this study, we use a 1-D diffusion-reaction model to calculate depth-resolved CO 2 production rates from soil CO 2 concentrations and surface efflux observations in a subalpine meadow in the East River watershed, CO. Modeled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 82 publications
(123 reference statements)
2
11
0
Order By: Relevance
“…These results reflect those of Winnick et al. (2020), who also found the transformation of CO 2 source and sink in the deep soil layer. Considering that these deep soil layers almost have no root distribution and the organic carbon content is also extremely low, the CO 2 dynamic there might be attributed to non‐biological processes such as soil gas transport (Maier et al., 2010) and geochemical CO 2 production or consumption (Rey, 2015; Sánchez‐Cañete et al., 2018).…”
Section: Discussionsupporting
confidence: 92%
“…These results reflect those of Winnick et al. (2020), who also found the transformation of CO 2 source and sink in the deep soil layer. Considering that these deep soil layers almost have no root distribution and the organic carbon content is also extremely low, the CO 2 dynamic there might be attributed to non‐biological processes such as soil gas transport (Maier et al., 2010) and geochemical CO 2 production or consumption (Rey, 2015; Sánchez‐Cañete et al., 2018).…”
Section: Discussionsupporting
confidence: 92%
“…The optimization of the model resulted in a C GW pCO 2 of 18,000 ppm, C wet pCO 2 of 44,000 ppm, F wc of 9*10 −11 mol L −1 s −1 , and a benthic hyporheic zone pCO 2 elevation (C hz -C) of 700 ppm. The best three optimization runs all had the same C GW and C wet values, with C GW values falling within the range of sub-soil (>30 cm) growing season pCO 2 values measured in a soil profile within the East River watershed (∼7,000-23,000 ppm; Winnick et al, 2020). Point measurements of standing waters within wetland areas were above the 25,000 ppm calibration of the EGM-5, though typically displayed values between 30,000-100,000 ppm supporting the elevated model optimization value.…”
Section: Model Resultsmentioning
confidence: 80%
“…During the sampled period, snow was present in the higher elevations and meltwater was contributing to the discharge ( Q ). The three major life zones within the basin are alpine, montane, and subalpine (Carroll et al., 2018; Hubbard et al., 2018) with the tree line at 3,500 m (Winnick et al., 2020). The modeled East River watershed comprises a range of land cover including conifer and aspen forests (32%), unvegetated rock (28%), grass and shrubland (23%), and wetlands (16%), with <1% of land as a mixture of human uses (U.S. Geological Survey, 2016) (Figure S1 in Supporting Information S1).…”
Section: Methodsmentioning
confidence: 99%
“…When the O 2 diffusion limit is combined with a linear or sublinear function that increases with soil moisture (i.e., representing greater substrate availability), the result is a triangular function with a fairly narrow range of optimum soil moisture, which agrees with the observation that SM is most limiting on R H when soils are relatively dry or approaching saturation (Reichstein et al., 2003). At high northern latitudes, these conditions may predominate during spring thaw (Oikawa et al., 2014; Winnick et al., 2020), which underscores the key role of SM in accurately modeling the corresponding carbon cycle transitions.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Järveoja et al found that the temperature sensitivity of R H in northern peatlands is enhanced in dry periods, possibly due to increased O 2 supply to heterotrophs. It has also been found to improve RECO estimation at wetland sites (Sulman et al, 2012) and where snowmelt also leads to an increase in soil water content in spring (Oikawa et al, 2014;Winnick et al, 2020). A vertically stratified soil column has been adopted in land models (dos Santos et al, 2021;Tao et al, 2017).…”
mentioning
confidence: 99%